REKONSTRUKSI HISTRORIS JIHAD PARA KYAI DAN KAUM SANTRI DAN IMPLEMENTASINYA DALAM MEWUJUDKAN SPIRIT NASIONALISME MEMPERTAHANKAN KEMERDEKAAN INDONESIA: this article had published in https://ecohumanism.co.uk/joe/ecohumanism/article/view/4076 - Rahman, Rahman; Rohman, Moh. Mujibur; Akbar, Ali; Ghozali Syaf’i, Achmad; Darusman, Darusman (TSAQAFAH, 2025)
RETRACTED (double submission) This article discusses the reconstruction of the history of the struggle of the kyai and santri in fighting for and defending Indonesian independence. This is important to do because recently the spirit of nationalism of the Indonesian people has begun to erode and some even consider it as an understanding that is contrary to Islam. By using a qualitative approach and data collection techniques through literature studies and historical facts, this paper shows that the true spirit of Nationalism needs to continue to be instilled in the souls of all the nation's children, because it is the result of the jihad of the kyai and the santri. This paper does not intend to deny the struggle of the heroes who did not come from the kyai and the santri, because those involved in the struggle are fighters who have sacrificed everything for the independence of Indonesia, of course in this case regardless of religion, ethnicity and race. The results of this study can at least provide input to policy makers that it is necessary to continuously instil the spirit of Nationalism by reviving the spirit of jihad to defend the State because it is still relevant to the condition of the nation. Jihad does not mean physical warfare against fellow children of the nation who are against the ideology of Nationalism, but providing continuous guidance on how the spirit of Nationalism is an inseparable part of Islamic teachings. For this reason, we ban the authors for 5 years publications in UNIDA Gontor. this article had published in https://ecohumanism.co.uk/joe/ecohumanism/article/view/4076Â